Hubungan Persepsi Tentang Vaksin Covid-19 Dengan Kecemasan Saat Akan Menjalani Vaksinasi Covid-19 Pada Masyarakat Di Desa Tembokrejo Tahun 2022 - Annisa Nur Nazmi; Nur Hidayatin; Linda Dwi Antika Hadi supaat (PROFESSIONAL HEALTH JOURNAL, 2022)
Sources of public concern regarding the Covid-19 vaccine are about the safety and efficacy of the vaccine, vaccine side effects, misunderstanding of the need for vaccination, lack of trust in the health care system, and also the lack of public knowledge of vaccine-preventable Covid-19 disease (Halpin, 2019). Anxiety Feeling experienced by the community can make people doubt or not willing to be vaccinated. The purpose of this study was to determine the relationship between perceptions about the Covid-19 vaccine and anxiety when undergoing a Covid-19 vaccination. The research method used cross sectional with 60 respondents was selected by purposive sampling technique. The Data analysis used statistical test fisher's Exact Test using SPSS 25 for windows obtained negative perceptions as many as 47 respondents (78.3%) and moderate anxiety as many as 43 respondents (71.7%) the significance value of fisher's Exact Test perceptions with anxiety in the community in Tembokrejo village was 0.004 < = 0.05 then H0 was rejected Ha was accepted which means there was a relationship between perceptions about the Covid-19 vaccine and anxiety when going to undergo Covid-19 vaccination in Tembokrejo village in 2022. Positive perceptions will cause mild anxiety while negative perceptions will cause moderate to severe anxiety in the community.